Publirreportaje en la prensa. Caso La Hora - Cordova Muñoz, Felix Arturo (2020)
The present work was based on the Advertorials in the press case `` La Hora '', in order to examine the journalistic texts that they handle in their printed and digital publications. The techniques used were through the observation of their audiovisual advertorials and those published on its website platform, bibliographic research of authors who speak about the corresponding topics, which allowed to know first-hand information on the subject of analysis of the case, being exposed in detail the characteristics of the contents that knew how to handle the newspaper '' La Hora '' and in depth the differences they have at the time of publishing their infomercials, standing out for their particular way of transmitting them to the general public, managing to mark in people's minds the type of products and services of which they promoted without that the reader realized that they were hybrid content, '' La Hora '' Without a doubt, it leaves its original patterns marked following the standards of traditional journalism and the new digital journalism in Ecuador, teaching us that good presentations can be made in our media to always keep the attention of our readers, confirming that the New generations of social communicators will always have to maintain ethics and professionalism and innovation in the different branches of the career, without leaving aside the rules of serious and objective journalism.